NF-κB signaling pathway-enhanced complement activation mediates renal injury in trichloroethylene-sensitized mice. (1st January 2018) - Liu, Min; Wang, Hui; Zhang, Jiaxiang; Yang, Xiaodong; Li, Bodong; Wu, Changhao; Zhu, Qixing
Abstract: Both NF-κB pathway and complement activation appear to be involved in kidney damage induced by trichloroethylene (TCE). However, any relationship between these two systems has not yet been established. The present study aimed to clarify the role of NF-κB in complement activation and renal injury in TCE-sensitized BALB/c mice. Mice were sensitized by an initial subcutaneous injection and repeated focal applications of TCE to dorsal skin at specified timepoints. NF-κB inhibitor pyrrolidine dithiocarbamate (PDTC) was injected (intraperitoneal) before the final two focal TCE challenges. In the experiments, mice had their blood and kidneys collected. Kidney function was evaluated via blood urea nitrogen (BUN) and creatinine (Cr) content; renal histology was examined using transmission electron microscopy (TEM). Kidney levels of phospho-p65 were assessed by Western blot and kidney mRNA levels of interleukin ( IL )- 1β, IL-6, IL-17, tumor necrosis factor ( TNF )- α, and p65 by real-time quantitative PCR. Presence of C3 and C5b-9 membrane attack complexes in the kidneys was evaluated via immunohistochemistry. The results showed there was significant swelling, vacuolar degeneration in mitochondria, shrinkage of microvilli, disappearance of brush borders, segmental foot process fusion, and glomerular basement membrane thickening (or disrobing) in kidneys from TCE-sensitized mice. In conjunction with these changes, serum BUN and Cr levels were increased and IL-1β, IL-6, IL-17, and TNFα mRNA levels were elevated. Levels of p65 and phospho-p65 protein were also up-regulated, and there was significant C3 and C5b-9 deposition. PDTC pretreatment attenuated TCE-induced up-regulation of p65 and its phosphorylation, complement deposition, cytokine release, and renal damage. These results provide the first evidence that NF-κB pathway has an important role in TCE-induced renal damage mediated by enhanced complement activation in situ .